2013
DOI: 10.1093/treephys/tps133
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen nutrition and drought hardening exert opposite effects on the stress tolerance of Pinus pinea L. seedlings

Abstract: Functional attributes determine the survival and growth of planted seedlings in reforestation projects. Nitrogen (N) and water are important resources in the cultivation of forest species, which have a strong effect on plant functional traits. We analyzed the influence of N nutrition on drought acclimation of Pinus pinea L. seedlings. Specifically, we addressed if high N fertilization reduces drought and frost tolerance of seedlings and whether drought hardening reverses the effect of high N fertilization on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 64 publications
3
45
1
3
Order By: Relevance
“…Studies with Picea abies L. and Pinus pinea L. seedlings, using low and high fertilization rates, indicated that NSC contents were positively and negatively correlated with fertilization rates, respectively (Kaakinen et al 2004;Villar-Salvador et al 2013). Stored N and NSC are functional attributes, indicative of seedling quality and a substantive body of evidence in the literature concludes that over-fertilization retards N storage (Millard and Grelet 2010;Villar-Salvador et al 2015).…”
Section: Impact Of Controlled Release Fertilizer Rate On Chinese Pinementioning
confidence: 99%
“…Studies with Picea abies L. and Pinus pinea L. seedlings, using low and high fertilization rates, indicated that NSC contents were positively and negatively correlated with fertilization rates, respectively (Kaakinen et al 2004;Villar-Salvador et al 2013). Stored N and NSC are functional attributes, indicative of seedling quality and a substantive body of evidence in the literature concludes that over-fertilization retards N storage (Millard and Grelet 2010;Villar-Salvador et al 2015).…”
Section: Impact Of Controlled Release Fertilizer Rate On Chinese Pinementioning
confidence: 99%
“…In recent years, there has been a trend to determine nursery fertilization in light of field performance on a specific site condition as well as seedling biomass and nutrient reserves accumulated during nursery growth (Hawkins et al 2005, Heiskanen et al 2009, Oliet et al 2009, Jonsdottir et al 2013, Villar-Salvador et al 2013. For example, in very dry Mediterranean environments some studies showed that seedlings with low nutrient concentration or content performed better (Trubat et al 2008, Cortina et al 2013, whereas other studies indicated that increased tissue nutrient reserves improves seedling field performance (Luis et al 2009, Cuesta et al 2010, Villar-Salvador et al 2012, Oliet et al 2013.…”
Section: Effect Of Pre-hardening Fertilization On Nursery and Field Pmentioning
confidence: 99%
“…O extravasamento de eletrólitos de células é uma reposta isiológica característica em vegetais submetidos aos diferentes tipos de estresse (RÄISÄNEN et al, 2009;VILLAR-SALVADOR et al, 2013;VOLKWEIS et al, 2014). Esse fenômeno é amplamente usado como um indicativo do nível de dano ou da tolerância ao estresse, sendo que menores valores para o extravasamento de eletrólitos indicam a maior integridade das membranas biológicas.…”
Section: Discussionunclassified
“…Alterações na condutância estomática, ajustamento osmótico, assimilação líquida de carbono e redução no crescimento da parte aérea com maior percentual de raízes são algumas evidências em estudos de condicionamento à deiciência hídrica (BAÑON et al, 2006;THOMAS, 2009;VILLAR-SALVADOR et al, 2013). Na produção de mudas por sementes de espécies lenhosas da flora brasileira, a heterogeneidade do crescimento aéreo é corriqueiramente observada dada a variabilidade genética das matrizes assim como o manejo no viveiro, gerando mudas com diferentes padrões de qualidade e onerando a classiicação antevendo a expedição (VOLKWEIS et al, 2014).…”
Section: )unclassified